FLOW OF FISCAL RESPONSIBILITY AMONG LAYERS OF GOVERNMENT: A CASE OF NIGERIA - Ogunlana Olarewaju Fatai; Lawal Arogundade Samod; Bello Al-Hassan Taiwo; Kolawole Bashir Olayinka (European Scientific Journal, ESJ, 2014)
The issue of fiscal federalism has for quite some time engaged the attention of scholars and policy makers in contemporary Nigeria. Several arguments have been put forward on the economic and political desirability for the practice of fiscal federalism in a country. While the political arguments are largely based on the heterogeneous characteristics of the different regions making up the country, the economic justification is usually based on the need to promote efficiency in the use of national resources. This paper examines the effect of fiscal decentralization on macroeconomic performance in Nigeria. The study employs three measures of fiscal decentralization namely revenue measure, expenditure measure and simultaneity measure to determine the extent, and the impact of fiscal decentralization on macroeconomic performance over the period 1980 to 2010. The overall objective of this study is to analyze the empirical effects of fiscal decentralization on some selected indicators of macroeconomic performance in Nigeria. The indicators include: economic growth, inflation rate, interest rate, and exchange in Nigeria. The Vector Autoregressive (VAR) estimator with lagged decentralization variables was employed using the E-views, version 7.0 to provide analytical support. The empirical findings are quite informative and offer evidence that the central objective of this study has been empirically investigated. There is, indeed, a connection between fiscal federalism and macroeconomic performance in Nigeria over the study period. The study suggests that faster economic growth may constitute additional benefit of fiscal decentralization beyond those already well recognized. This finding conforms to a strand of the literature that establishes links between fiscal decentralization, public sector efficiency and macroeconomic stability.